2015
DOI: 10.15809/irriga.2015v1n2p158
|View full text |Cite
|
Sign up to set email alerts
|

Acurácia De Um Mini-Lisímetro De Pesagem Eletrônica De Baixo Custo

Abstract: ACURÁCIA DE UM MINI-LISÍMETRO DE PESAGEM ELETRÔNICA DE BAIXO CUSTO  MARCIO DA SILVA VILELA¹; FERNANDO RODRIGUES CABRAL FILHO²; MARCONI BATISTA TEIXEIRA³; ALISSON MACENDO AMARAL4; LUCAS MELO VELLAME5 E FREDERICO ANTONIO LOUREIRO SOARES3 1 Engenheiro Elétrico, Prof. Doutor, Instituto Federal Goiano, Campus Rio Verde, GO. msvilela@yahoo.com.br2 Graduando em Agronomia, Departamento de Hidráulica e Irrigação, Instituto Federal Goiano, Campus Rio Verde, GO. fernandorcfilho@hotmail.com3 Engenheiro Agrônomo, Prof. Dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
1
1
0
3
Order By: Relevance
“…The hysteresis error of 0.031 kg, representing 0.03% (ES) or 0.02 mm, is similar to those reported by Vilela et al (2015), who obtained 0.02 kg when calibrating a mini weighing lysimeter, and by Vellame et al (2012), who obtained 0.019% and 0.015% (ES). These errors were virtually the same.…”
Section: Resultssupporting
confidence: 88%
“…The hysteresis error of 0.031 kg, representing 0.03% (ES) or 0.02 mm, is similar to those reported by Vilela et al (2015), who obtained 0.02 kg when calibrating a mini weighing lysimeter, and by Vellame et al (2012), who obtained 0.019% and 0.015% (ES). These errors were virtually the same.…”
Section: Resultssupporting
confidence: 88%
“…The data determined by the calibration of the lysimeters exhibited linear adjustments with high determination coefficient ( Figure 4). Several extant studies also observed high coefficients of determination that reached values equal or similar to R 2 = 0.99 (Mariano et al, 2015;Vilela et al, 2015;Carvalho et al, 2013;Lima et al, 2013). Additionally, angular and linear coefficients exhibited similar values in all the lysimeters (Figure 4).…”
Section: Resultsmentioning
confidence: 93%
“…Vilela et al (2015) verificou que o erro de histerese, não linearidade, repetitividade e o erro máximo absoluto oriundos no processo de calibração, não podem ser desconsiderados no processo de calibração, principalmente quando em relação aos desvios. Depois do erro máximo absoluto e o de não-linearidade os que mais influenciaram na precisão do equipamento foi a histerese seguido da repetitividade com erro médio de 3,5 e 2,8% respectivamente.…”
Section: Resultsunclassified